Practical application of range areas monitoring - Semenye, P.P. (1981)
Discusses the practical application of range areas monitoring. Examines the herd structure of Elangata Wuas, Olkarkar and Merueshi group ranches. presents and discusses herd and flock demography including herd structure, fertility & mortality; out put including milk yields, weight gain of calves, steers & small stock, small stock weights, and off take and in-take rates; and input data including treatments and preventive medicine, supplementary feeding, reserved grazing for calves & management